Early cambrian metamorphic zircon in the Northern Pinjarra Orogen: Implications for the structure of the west Australian craton margin - Markwitz, V.; Kirkland, Chris; Evans, Noreen (Geological Society of America, 2017)
© 2016 Geological Society of America.The Mesoproterozoic Pinjarra Orogen formed when present-day India and Australia amalgamated to form Gondwana. Outcrop of the Pinjarra Orogen is limited to the Leeuwin, Mullingarra, and Northampton Complexes, which are exposed as basement inliers in the Paleozoic to Mesozoic Perth and Southern Carnarvon Basins. We used U-Pb zircon geochronology to date Pinjarra Orogen basement rocks from the Wendy-1 drill core, which intersects the Paleozoic Tumblagooda Sandstone and its underlying paragneiss basement east of the Northampton Complex. Our results suggest an Early Cambrian (526.3 ± 12 Ma) metamorphic age for this basement domain, which is uncharacteristic for the nearby Northampton Complex, but correlates well with the much more distant Leeuwin Complex. Detrital ages between 1120 Ma, 1210 Ma, and 1530 Ma dominate the zircon cargo of this basement sample, which may have been sourced from the Albany-Fraser Orogen to the south and east. An Archean detrital zircon component is also identified from one concordant analysis, and from radiogenic Pb-loss modeling. These results have important implications for the crustal architecture of the western margin of the West Australian craton and for correlating domains of the Mesoproterozoic Pinjarra Orogen in reconstructions of Gondwana. Our data suggest that the basement below the Perth Basin is more segmented than previously assumed. Evidence for a common Indian-Australian tectonometamorphic event in the Late Neoproterozoic to Early Cambrian is not limited to the Leeuwin Complex in the southwest corner of present-day Western Australia but also now identified in basement rocks in the Northampton area. These results confirm the in situ formation of Pinjarra Orogen basement complexes in the Mesoproterozoic with a metamorphic reactivation in the Neoproterozoic-Cambrian during the collision with present-day India.